2018
DOI: 10.1037/xhp0000552
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual biases during cued task switching relate to decision process differences between children and adults.

Abstract: Previous work suggests that children engage preparatory processing differently than adults in cued task switching. One potential consequence is that they are differentially biased by visual properties of the stimuli, for example, target-choice similarity. We tested this possibility in 215 children and young adults ranging from 6 to 27 years of age. Participants played a cue-target game with varying levels of working memory and attentional demand where they matched multidimensional stimuli according to a cued d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 93 publications
(152 reference statements)
1
4
0
Order By: Relevance
“…The 14-to 16-year-old group was not significantly different from adults in their accuracy across the first five levels and in their response times across all six levels. This result was largely consistent with what has been found behaviorally with versions of this task-that adult-like performance is seen around age 14 years (Bauer et al, 2017;Martinez et al, 2018). It is intriguing to speculate, however, that ages 11-13 years may be in a transitional period where fixation patterns begin to change prior to behavioral performance; 11-to 13year-olds for some task levels (e.g., Level 2 during the cue period) had equivalent fixation times to adults.…”
Section: Children's Task-switching Performance Improves With Agesupporting
confidence: 90%
See 3 more Smart Citations
“…The 14-to 16-year-old group was not significantly different from adults in their accuracy across the first five levels and in their response times across all six levels. This result was largely consistent with what has been found behaviorally with versions of this task-that adult-like performance is seen around age 14 years (Bauer et al, 2017;Martinez et al, 2018). It is intriguing to speculate, however, that ages 11-13 years may be in a transitional period where fixation patterns begin to change prior to behavioral performance; 11-to 13year-olds for some task levels (e.g., Level 2 during the cue period) had equivalent fixation times to adults.…”
Section: Children's Task-switching Performance Improves With Agesupporting
confidence: 90%
“…Fifty-four adults, ages 18-29 years, and 63 children, ages 6-16 years, were initially recruited for this study. Previous studies (Bauer et al, 2017;Martinez et al, 2018) utilizing a similar cued taskswitching paradigm found reasonable effects at a similar sample size, motivating the sample size for this study. The age range for analysis was narrowed for adults to 18-27 years to overcome limited sampling in ages 28-29 years, and for children to 8-16 years to have complete neuropsychological assessments.…”
Section: Participantsmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior work has generally demonstrated that children have more cautious responses than adults (Manning et al, 2021; Nordmeyer et al, 2016; Ratcliff et al, 2012; Schneider & Frank, 2016), though in some tasks children make more impulsive, less cautious decisions than adults (Martinez et al, 2018). Here, we found that, in general, children had less cautious responses than adults and that children had more similar decision thresholds for correct and incorrect responses.…”
Section: Discussionmentioning
confidence: 99%